A Revised Structure for the Glycolipid Terminus of Escherichia coli K5 Heparosan Capsular Polysaccharide - Lufeng Yan (Biomolecules, 2020)
The structure of heparosan capsular polysaccharide (CPS) has been determined using enzymatic digestion with nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry. Previous errors in the assignment of the glycolipid acceptor structure, from which heparosan is extended, have been corrected. The structure of heparosan CPS is GlcNAc α-1,[4GlcA β-1,4GlcNAc α-1,]n4GlcA β-1,[4Kdo β-2,7Kdo β-2,]0 or 14Kdo β-2,7Kdo β-2,4Kdo β-2,7Kdo β-2,4Kdo β-2,7Kdo β-2,4Kdo β-PG-I (C16:0 or C18:0) (where n is ~250 for a CPS of 100 kDa).